Sekolah Tinggi Perikanan Terpadu Di Bagansiapiapi Dengan Pendekatan Eko-Arsitektur - Siswoyo, Sindi; Aldy, Pedia; Susilawati, Mira Dharma (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Rokan Hilir has good potential for fisheries, and it has been proved since 2007, the production of fishery in Rokan Hilir Regency has been above 50.000 tons, (BPS, 2015). That potential needs to beaccomodated to education world to develop and increase production of fisheries in Rokan Hilir, considering historically Bagansiapiapi has ever been known as the second largest producer of fisheries production in the world. The planned means is High School of fishery. In High School of Fishery design, the design approach applied is echo-architecture design principle in order tosinergize the building with the environment. In order to emphasize the design “Bahtera Edukasi” concept is applied which is gotten from historical value of Bagansiapiapi. There are some criteriaof echo-architecture design principle: (1) Low Energy Usage; (2) Responsive to the Climate; and (3) environmentally Friendly. In this High School of Fishery design has 3 principal functions, theyare management, education, and dormitory which applies echo-architecture in order to make High School of Fishery responsive to the environment.Keywords: Bagansiapiapi High School of Fishery, Eco-Architecture, Bahtera Edukasi.